National audubon society first field guide : fishes. - Smith, C. Lavett (New York Scholastic, 2000)
Explores the world of fishes, discussing their classification, anatomy, behavior, and habitat, and providing photographs and detailed descriptions of individual taxonomic families.
Keywords: Fishes -- Juvenile literature; Fishes -- North America -- Juvenile literature; Fishes